PROTEKSIONISME UNI EROPA TERHADAP IMPOR PANEL SURYA TIONGKOK TAHUN 2013 - Adika Sari, Ni Putu Ayu; Suwecawangsa, Adi Putra; Intan Parameswari, Anak Agung Ayu (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
This research aims to explain the reasons of European Union implementing an anti-dumping policy on imports of Chinese solar panels in 2013. This study uses a qualitative explanative method with concept protectionism. The European Union is one of the regions that depends on imports of fossil fuels. Therefore, the European Union pays great attention to renewable energy sectors especially solar panels. The European Union, which initially took the lead in the production of solar panels, is starting to be pushed back by the presence of its competitor, China. In response to fierce competition in the solar panel sector, the European Union implemented a protectionist policy in the form of anti-dumping by targeting the selling price of Chinese products which was far below the minimum price. Keywords: European Union, China, Anti-dumping, Solar Panels